On the Use of Dynamical Diffraction Theory To Refine Crystal Structure from Electron Diffraction Data: Application to KLa5O5(VO4)2, a Material with Promising Luminescent Properties - Colmont, Marie; Palatinus, Lukas; Huvé, Marielle; Kabbour, Houria; Saitzek, Sébastien; Djelal, Nora; Roussel, Pascal (Inorganic chemistry, 2016)
A new lanthanum oxide, KLa5O5(VO4)2, was synthesized using a flux growth technique that involved solid-state reaction under an air atmosphere at 900 °C. The crystal structure was solved and refined using an innovative approach recently established and based on three-dimensional (3D) electron diffraction data, using precession of the electron beam and then validated against Rietveld refinement and denisty functional theory (DFT) calculations. It crystallizes in a monoclinic unit cell with space group C2/m and has unit cell parameters of a = 20.2282(14) Å, b = 5.8639(4) Å, c = 12.6060(9) Å, and β = 117.64(1)°. Its structure is built on Cresnel-like two-dimensional (2D) units (La5O5) of 4*3 (OLa4) tetrahedra, which run parallel to (001) plane, being surrounded by isolated VO4 tetrahedra. Four isolated vanadate groups create channels that host K(+) ions. Substitution of K(+) cations by another alkali metal is possible, going from lithium to rubidium. Li substitution led to a similar phase with a primitive monoclinic unit cell. A complementary selected area electron diffraction (SAED) study highlighted diffuse streaks associated with stacking faults observed on high-resolution electron microscopy (HREM) images of the lithium compound. Finally, preliminary catalytic tests for ethanol oxidation are reported, as well as luminescence evidence. This paper also describes how solid-state chemists can take advantages of recent progresses in electron crystallography, assisted by DFT calculations and powder X-ray diffraction (PXRD) refinements, to propose new structural types with potential applications to the physicist community.